ANALISIS KESIAPAN PSIKOLOGIS GURU SEKOLAH DASAR DALAM IMPLEMENTASI MEDIA PEMBELAJARAN INTERAKTIF BERBASIS CANVA DI SD NEGERI 18 BANDA ACEH - Suardi, Helmi; Sari, Nena Puspita; Ramadani, Mentari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The digital transformation of education requires teachers to integrate technology as part of interactive and student-centered instructional strategies. The use of the graphic design application Canva has become an alternative form of digital learning media in elementary schools; however, its effectiveness is strongly influenced by teachers’ psychological readiness. This study aims to analyze the psychological readiness of elementary school teachers in implementing Canva-based interactive learning media at SD Negeri 18 Banda Aceh and to identify the challenges encountered in its use. The research employed a mixed-methods approach with a sequential explanatory design. Data were collected through questionnaires, interviews, and documentation. The research subjects consisted of all 20 teachers, with 3 teachers selected as interview informants. Quantitative data were analyzed using descriptive statistics, while qualitative data were examined through data reduction, data display, and conclusion drawing. The findings indicate that teachers’ psychological readiness falls into the very ready category, with an average score of 3.42 (85.4%). The cognitive aspect scored 3.50 (87.5%), the affective aspect 3.42 (85.4%), the psychomotor aspect 3.50 (87.5%), and the infrastructure aspect 3.25 (81.2%). Teachers understand the benefits of Canva, demonstrate positive attitudes, and are able to operate its basic features in developing learning media. The identified challenges include limited internet connectivity, restrictions of free-account features, and limited time to prepare instructional materials. This study concludes that teachers are psychologically ready to implement Canva as an interactive learning medium; however, optimizing its utilization requires adequate facilities and continuous training support.